PENYULUHAN KESEHATAN REPRODUKSI TENTANG FLOUR ALBUS PADA REMAJA - Nuari Andolina (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2022)
ABSTRACT In the health life of a woman there are several complaints of disease, one of the complaints that is very disturbing is fluor albus (leucorrhoea). Fluorine albus is excessive fluid that comes out of the vagina. Vaginal discharge can be physiological (under normal circumstances) but can also be pathological (due to disease). Not many women know what vaginal discharge is and sometimes take this problem lightly. Even though vaginal discharge cannot be taken lightly, because the consequences of this vaginal discharge can be very fatal if it is not treated slowly. The purpose of this outreach activity is to make young women understand the causes and treatment of vaginal discharge because if not treated vaginal discharge can interfere with the health of the reproductive organs so that it can lead to infertility and pregnancy outside the womb, vaginal discharge can also be an early symptom of cervical cancer, which can lead to death. This activity was carried out at the Youth Posyandu. This activity begins by asking questions about the knowledge of young women about vaginal discharge. Followed by giving material using power point. The result of this activity is that there is an increase in adolescent knowledge about vaginal discharge by 60%. This activity is the first step to improve reproductive health, especially young women who are prospective mothers who will give birth to the next generation of this nation.